Comparable CD4 and CD8 T cell responses and cytokine release after at-birth and delayed BCG immunisation in infants born in Australia. Issue 35 (29th July 2016) - Ritz, Nicole; Casalaz, Dan; Donath, Susan; Tebruegge, Marc; Dutta, Binita; Connell, Tom G.; Robins-Browne, Roy; Britton, Warwick J.; Hanekom, Willem A.; Curtis, Nigel
Abstract: Background: More than 120 million doses of BCG vaccine are administered worldwide each year. Most infants are given BCG at birth in accordance with WHO recommendations. However, the effect of the maturing neonatal immune system on the immune response and protection conferred by BCG remains uncertain. Previous studies investigating the influence of age at immunisation on the immune response induced by BCG have reported conflicting results. This study compared BCG given at birth and at two months of age in infants in Australia. Methods: Infants born in Melbourne were randomly allocated to immunisation with BCG-Denmark at birth or two months of age. Ten weeks after immunisation, anti-mycobacterial immune responses were measured in a whole blood assay using intracellular cytokine assays and xMAP multiplex cytokine analysis. Results: Result from 98 BCG-immunised infants were included in the final analysis. BCG immunisation at birth ( n  = 54) and at 2 months of age ( n  = 44) induced comparable proportions of mycobacteria-specific cytokine-producing CD4 and CD8 T cells, as well as comparable proportions of polyfunctional (TNF + IL-2 + IFN-γ + ) CD4 T cells. Concentrations of cytokines in supernatants were also similar in both groups. Conclusions: Cellular immunity measured 10 weeks after BCG immunisation was similar in infants given BCG at birth and in those given BCG at 2 months of age. Although definitive correlates of protection against TB remain uncertain, these results suggest that delaying BCG immunisation does not confer any immunological advantage in cellular immunity.